(untitled) (Bangladesh Journal of Animal Science, 2012)
The present research was undertaken to explore the maturation of buffalo oocytes using bovine follicular fluid (BFF) and bovine serum albumin (BSA), as well as subsequent fertilization using cattle spermatozoa. The cumulus oocyte complexes (COCs) were collected by aspiration of slaughterhouse buffalo ovaries. Maturation was performed in TCM 199 supplemented with 10% BFF, 5% BSA or without supplementation (control). The COCs were fertilized in Brackett and Oliphant (BO) medium using capacitated fresh cattle spermatozoa. It was observed that the percentage of COCs reached to M-II stages were 40.78±3.84, 65.74±2.39 and 67.52±0.85; normal fertilization (formation of 2 pronuclei) were 23.28±3.00, 29.30±0.73 and 30.52±1.21 for control, 10% BFF and 5% BSA supplementation, respectively. The supplementation of BFF (10%) and BSA (5%) were given similar results on maturation and increased significantly (p<0.05) than that of the control. It was observed that cattle spermatozoa were fertilized by the buffalo oocytes and the fertilization rate was 23.28% to 30.52% in BFA and BSA supplemented media, respectively. It can be concluded that buffalo oocytes might be fertilized using capacitated cattle spermatozoa and both 10% BFF and 5% BSA could be supplemented in maturation media to enhance the maturation rate as well as fertilization of buffalo oocytes. http://dx.doi.org/10.3329/bjas.v41i1.11969